Analisis emisi karbondioksida ditinjau dari penggunaan kendaraan berbasis aplikasi di Kecamatan Sukolilo Surabaya - Raffinet, Zarin; Yayok Suryo Purnomo (Program Studi Akuntansi IKOPIN, 2022)
Motor vehicles that are often used can have a serious impact, especially on the environment. Congestion, noise and exhaust emissions caused by uncontrolled use of motor vehicles. The research method used is a quantitative method that performs CO2 emission calculations using the Mobile 6 equation and performs data analysis with regression tests using the SPSS Version 19 program and conducts interviews on 59 vehicle users taken at random sampling. The total results of CO2 emissions conditions before the covid-19 pandemic on Jalan Nginden Semolo amounted to 1670088.568 kg / year, on Jalan Arief Rahman Hakim amounted to 3287922.045 kg / year while on Jalan Kertajaya Indah amounted to 4129273.85 kg / year. So that the total CO2 emissions in Sukolilo Subdistrict amounted to 9087284,469 kg / year. Changes in CO2 emissions occurred in the form of the transfer of CO2 emissions from private vehicles to online motorcycles and online cars by 17.01% (25,412.03 tons of CO2/year) and 14.9% (22,300.35 tons of CO2/year) respectively. The selection of online motorcycles turned out to have one factor that had a significant effect, namely the traffic congestion factor. As for the selection of online cars is influenced by 2 significant factors, namely the limitation factor of parking space and more comfortable for travel.